The golden hoard : myths and legends of the world - McCaughrean, Geraldine; Willey, Bee (New York, N.Y. : M.K. McElderry, 1996)
A collection of twenty-two myths and legends, retold from many lands and many cultures.
How music was fetched out of heaven (a Mexican myth) -- Whose footprints? (a myth from the Gold Coast) -- The death of El Cid (a Spanish legend) -- The man who almost lived forever (a Mesopotamian legend) -- Stealing heaven's thunder (a Norse myth) -- Anansi and the mind of God (a West Indian myth) -- How men and women finally agreed (a Kikuyu myth) -- First snow (a Native American myth).
Keywords: Tales; Mythology -- Juvenile literature; Legends; Folklore; Mythology; Legends; Mythology; Tales; Juvenile works